IMPLEMENTATION OF ACADEMIC SUPERVISION IN 13TH STATE PRIVATE HIGH SCHOOL TANJUNG BALAI CITY - Beni, Joko; Hanum, Azizah; Zein, Achyar (UIN Sumatera Utara Medan, 2023)
This research is to describe the Implementation of Academic Supervision at State Junior High School 13 Tanjungbalai City which aims to reveal that the Planning for Academic Supervision at State Junior High School 13 Tanjungbalai City, Implementation of the Academic Supervision Program at State Junior High School 13 Tanjungbalai City, Evaluation of Academic Supervision at State Junior High School 13 Tanjungbalai City. This research uses a qualitative type of research with a phenomenological approach, using data collection techniques in the form of observation, interviews and documentation studies. The results of this research reveal three findings, namely that the Academic Supervision Planning at State Junior High School 13 Tanjungbalai City has been structured correctly in accordance with existing provisions. The implementation of the Academic Supervision Program at State Junior High School 13 Tanjungbalai City is not yet optimal due to inadequate facilities and infrastructure. Evaluation of Academic Supervision at State Junior High School 13 Tanjungbalai City has been carried out in accordance with existing procedures. From the explanation above, it can be concluded that the implementation of academic supervision must have a work program, carry out supervision in every program implementation up to evaluation, namely measuring and assessing the results of the performance that has been carried out.